2022
DOI: 10.1002/csr.2233
|View full text |Cite
|
Sign up to set email alerts
|

The effect of green strategies and eco‐innovation on Mexican automotive industry sustainable and financial performance: Sustainable supply chains as a mediating variable

Abstract: This work focuses on the study of how green strategies (GBS) and eco-innovation (EI) contribute to increasing sustainable and financial performance in the context of the Mexican manufacturing industry, and whether these relationships are mediated by the practices involved in sustainable supply chains (SSCs). This analysis is carried out through an empirical study of a sample of 460 companies in the automotive industry. The results reveal direct positive effects of GBS and EI on performance both, sustainable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 142 publications
(217 reference statements)
1
23
0
2
Order By: Relevance
“…Moreover, the results of the empirical study confirmed the acceptance of H3, which confirms the positive impact of green innovation on the green supply chain performance. This result was in agreement with several current studies that provided empirical evidence for the positive impact of green innovation on the green supply chain performance (Bag et al, 2022;Fernando et al, 2019;Rodr ıguez-Gonz alez et al, 2022). Green innovation is one of the main determinants of enhancing green supply chain performance and sustainable performance (Wong et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, the results of the empirical study confirmed the acceptance of H3, which confirms the positive impact of green innovation on the green supply chain performance. This result was in agreement with several current studies that provided empirical evidence for the positive impact of green innovation on the green supply chain performance (Bag et al, 2022;Fernando et al, 2019;Rodr ıguez-Gonz alez et al, 2022). Green innovation is one of the main determinants of enhancing green supply chain performance and sustainable performance (Wong et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The context of Jordanian food and beverages manufacturing firms is one of the contexts that did not pay much attention to by researchers in the field of big data. Thus, this paper provided interesting results by emphasizing the importance of big data analytics capabilities in promoting green innovation and improving the green supply chain performance according to the NRBV theory, and thus these organizational, administrative and human capabilities can be used to enhance the value of big data to improve the level of environmental readiness of these firms (Rodríguez‐González et al. , 2022; Fernando et al.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Despite the important role of BDA in enhancing sustainable organisational performance (Cetindamar et al, 2022;Chatterjee et al, 2022a, b), creating competitive advantage (Behl et al, 2022;Shah, 2022), and raising the GSCP, the role of GSC innovation (GSCI) in enhancing the GSCP is still of great importance in explaining the ability of the GSC to preserve the environment in manufacturing firms (Rodr ıguez-Gonz alez et al, 2022). Several scholars have confirmed (Chang, 2011;Roh et al, 2022) that GSCI is an important activity to promote green initiatives within firms.…”
Section: Introductionmentioning
confidence: 99%